Challenges When Using Grounded Theory: A Pragmatic Introduction to Doing GT Research. Issue 1 (6th March 2018) - Timonen, Virpi; Foley, Geraldine; Conlon, Catherine
The grounded theory (GT) method is widely applied, yet frequently misunderstood. We outline the main variants of GT and dispel the most common myths associated with GT. We argue that the different variants of GT incorporate a core set of shared procedures that can be put to work by any researcher or team from their chosen ontological and epistemological perspective. This "shared core" of the GT method is articulated as the principles of (1) taking the word "grounded" seriously, (2) capturing and explaining context-related social processes, (3) pursuing theory through engagement with data, and (4) pursuing theory through theoretical sampling. In this article, we have put forward, in a nutshell, a distillation of core principles underpinning existing GT approaches that can aid further engagement with the different variants of GT. We are motivated by the wish to make GT more comprehensible and accessible, especially for researchers who are new to the method.